Boredom as the originator of a desideratum - reflections on the creative and suppressive consequences of boredom in the school context - Zeißig, Anke (Frontiers in Sociology, 2023)
Bored children begin to draw, do crafts, to fidget - or they do something bad. Others fall silent, withdraw, or become lethargic. Research on school-related boredom has focused primarily on the negative consequences of boredom, such as decreased cognitive performance, motivation or attentativeness, or disruptiveness. These negative aspects of boredom can be contrasted by the notion that boredom can promote creative performance. This paper reflects on boredom's creative and suppressive consequences as an interplay of personality traits and behavioral possibilities in school situations, on the one hand, and as an interplay of situational experiences with constituent developmental processes on the other. It is proposed that boredom is a gauge of the learner's resonance with school content, learning and/or developmental relationships. Boredom indicates a psychological need and its desideratum. Thus, both creative and suppressive potentials are inherent in boredom.